Dynamic Interferometry Lithography on a TiO2 Photoresist Sol-Gel for Diffracting Deflector Module. (9th March 2017) - Gâté, V.; Berthod, L.; Langlet, M.; Vocanson, F.; Verrier, I.; Veillas, C.; Kaminski, A.; Parriaux, O.; Jourlin, Y.
Abstract : Solar electricity is one of the most promising renewable energy resources. However, the ratio module's cost/energy produced remains a major issue for classical photovoltaic energy. Many technologies have been developed to solve this problem, by using micro- or nanostructuring on the solar cell or on the module. These kinds of structuring are often used as antireflection and light-trapping tools. In the meantime, other solar technologies are considered, such as concentration photovoltaic modules. This article presents a module combining both approaches, that is, nanostructures and concentration, in order to increase the module's profitability. Sol-gel derived TiO2 diffraction gratings, made by dynamic interferometric lithography, are added on the top of the glass cover to deflect unused light onto the solar cell, increasing the module efficiency.